Geo-Sheet: Interactive GeoGebra-integrated learning material to enhance students’ creative mathematical reasoning in analytic geometry - Titin Masfingatin; Ika Krisdiana; Reza Kusuma Setyansah (FKIP Universitas Muhammadiyah Prof. DR. HAMKA, 2026)
In analytic geometry instruction, students’ reasoning often remains procedural, limiting opportunities to develop Creative Mathematical Reasoning (CMR). CMR refers to the ability to construct reasoning that is novel to the learner, justified as plausible, and grounded in intrinsic mathematical properties. This study aimed to design and evaluate Geo-Sheet, a GeoGebra-integrated interactive learning material intended to support students’ CMR in analytic geometry. The research involved 30 undergraduate students enrolled in an Analytic Geometry course in a Mathematics Education program at a private university in East Java, Indonesia. An Educational Design Research (EDR) approach was employed, consisting of preliminary and formative evaluation phases (self-evaluation, expert review, one-to-one, small group, and field testing). Geo-Sheet was assessed in terms of validity, practicality, and potential effect. Expert judgment indicated high validity (Aiken’s V = 0.82), and student questionnaires showed high perceived practicality (70% in the high category). Pre- and post-test results, supported by observations and interviews, revealed improvements across CMR indicators. These findings suggest that systematically designed GeoGebra-based materials that integrate dynamic visualization and guided exploration have the potential to create productive learning conditions for the development of higher-order mathematical reasoning.